IMPROVEMENT OF THE FISCAL POLICY OF UKRAINE UNDER THE CONDITIONS OF THE FORMATION OF A DIGITAL ECONOMY (INNOVATIVE ECONOMY, 2022)
Danylkiv Kh.P., Dropa Ya.B., Petyk M.I., Havran V.Ya. IMPROVEMENT OF THE FISCAL POLICY OF UKRAINE UNDER THE CONDITIONS OF THE FORMATION OF A DIGITAL ECONOMYPurpose. The purpose of the scientific work is to determine directions for improving the state's fiscal policy in the context of digitalization of the financial system and strengthening of European integration processes in Ukraine.Methodology of research. To achieve the defined goal, a complex of modern scientific research methods was used, in particular: logical – to gradually systematize the theoretical and practical principles of research; induction and deduction – for formulating well-founded conclusions and proposals; analysis and synthesis – to identify the factors that determine the fiscal policy of the state; statistical methods (grouping, comparison, series of dynamics) – for forming a data array and conducting an analysis of the effectiveness of fiscal policy; tabular and graphical methods, structural analysis – for analyzing the structure and dynamics of budget revenues and expenditures and determining the effectiveness of the fiscal policy.Findings. The article examines the fiscal policy from the point of view of the complex of financial actions of the government to ensure the possibility of financing a certain amount and ratio of budget expenditures, the organization of an optimal system of inter-budgetary relations, and the creation of an effective mechanism for taxation of economic entities and the country's population. The dual nature of fiscal policy, which includes two components: tax policy and budget expenditure policy, is revealed. The need to coordinate the government's activities in the direction of mobilizing tax revenues of the budget system and implementing budget expenditures to ensure the social and economic development of the national economy is emphasized.Fiscal policy tools are highlighted from the point of view of the set of means used in the process of withdrawing part of the funds from business entities and the population to ensure the mobilization of a sufficient amount of financial resources in the country's budget system. The fiscal mechanism is presented in terms of tax and budget components, which interact with each other, help to redistribute GDP, and have the appropriate tools. Its purpose is well-founded - attracting sufficient amounts of financial resources into the budget system to fulfill the functions and tasks assigned to it by the state.A close correlation between the volume of mobilized taxes and the number of budget expenditures is argued. It is emphasized that the implementation of an effective budget and tax policy can improve the investment climate in the country and accelerates the rate of economic growth. The effectiveness of the domestic tax policy was assessed using the analysis of the dynamics and structure of tax revenues to the budget system during 2010-2021. The negative impact on the development of the economy of Ukraine was revealed by the following factors, which caused the emergence of many constructive problems: the conduct of military operations on the territory of the country, the far from the optimal situation of the national market of goods and services, the drop in household incomes, the imbalance of the economy, etc.The areas of improvement of the tax policy in Ukraine in the conditions of the strengthening of the European integration processes are defined, and the necessity of introducing a program-target method in the management of budget expenditures is argued.The dynamics and structure of expenditures of the state and local budgets of Ukraine according to functional and economic classification are analyzed, and the need to improve inter-budgetary relations to increase the financial base of local self-government is emphasized. Directions for improving the domestic budget policy to turn it into a tool for ensuring the country's economic development are proposed.The main problems of implementation are outlined and ways to improve the state's debt policy from the point of view of its relationship with the tax and expenditure component of the budget system are determined. The main areas of improvement of the fiscal policy of the state are determined to increase its transparency with the help of participatory budgeting, the introduction of a system of electronic services, and the use of innovative digital technologies in public finances.Originality. The negative fiscal factors restraining the development of the national economy were determined using an analysis of the structure and dynamics of revenues and expenditures of the budget system; directions for improving the domestic tax policy and the policy of budget expenditures to stimulate economic growth are proposed; the main problems are identified and the ways of improving the debt policy of Ukraine in the conditions of European integration are substantiated; the expediency of using modern digital technologies to improve the fiscal policy of Ukraine is argued.Practical value. The results of the conducted research on the formation and implementation of fiscal policy in the conditions of the expansion of digital technologies will help the government of Ukraine to transform the policy in the field of taxes, budget expenditures, and public debt into the main tool for ensuring the country's development in the conditions of strengthening the processes of European integration.Key words: fiscal policy, taxes, budget expenditures, public debt, participatory budget, electronic services, Prozoro, public procurement, digital economy.
Keywords: fiscal policy; taxes; budget expenditures; public debt; participatory budget; electronic services; Prozoro; public procurement; digital economy.